Evaluation of the Quidel QuickVue Test for Detection of Influenza A and B Viruses in the Pediatric Emergency Medicine Setting by Use of Three Specimen Collection Methods - Agoritsas, Konstantinos (American Society for Microbiology, 2006)
The Quidel QuickVue influenza test was compared to viral culture and reverse transcriptase PCR by the use of three different respiratory specimen types. Of 122 pediatric subjects enrolled, 59 had influenza virus infections: 44 were infected with influenza A virus and 15 were infected with influenza B virus. The sensitivity of the QuickVue test was 85% with nasopharyngeal swabs, 78% with nasal swabs, and 69% with nasopharyngeal washes. Specificities were equivalent (97% to 98%) for all three collection methods.